2004
DOI: 10.1016/j.visres.2004.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The peculiar nature of simultaneous colour contrast in uniform surrounds

Abstract: We present evidence from asymmetric colour matching experiments which strongly suggests that uniform surrounds evoke induction effects of a very peculiar nature, not representative of colour induction effects in variegated surrounds. Given the widespread use of uniform surrounds in studies of colour vision, this finding is of interest in relation to a number of current research issues, such as contrast coding of colour, functionally equivalent surrounds and colour constancy. A framework that systematises the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 55 publications
8
69
0
Order By: Relevance
“…The first one is necessary because targets embedded in uniform surrounds have been noted to assume a dual colour impression reminiscent of perceptual transparency (Metelli, 1970), particularly when the contrast between target and surround is low Masin & Idone, 1981;Brown & MacLeod, 1997;Mausfeld, 1998;Ekroll et al, 2002Ekroll et al, , 2004. According to our experience, the target is then perceived as consisting of two layers, whereby one layer is perceived as coextensive with the target region and the other as extending across both the target and the surround.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The first one is necessary because targets embedded in uniform surrounds have been noted to assume a dual colour impression reminiscent of perceptual transparency (Metelli, 1970), particularly when the contrast between target and surround is low Masin & Idone, 1981;Brown & MacLeod, 1997;Mausfeld, 1998;Ekroll et al, 2002Ekroll et al, , 2004. According to our experience, the target is then perceived as consisting of two layers, whereby one layer is perceived as coextensive with the target region and the other as extending across both the target and the surround.…”
Section: Introductionmentioning
confidence: 81%
“…Our arguments in favour of these claims are based on many seemingly disparate and unrelated lines of evidence and recent developments in our understanding of simultaneous colour contrast (Brown & MacLeod, 1997;Gordon & Shapley, 2006;Hansen, Walter, & Gegenfurtner, 2007;Ekroll, Faul, Niederée, & Richter, 2002;Ekroll, Faul, & Niederée, 2004;Ekroll & Faul, 2009;Ekroll, Faul, & Wendt, 2011;Faul, Ekroll, & Wendt, 2008). The main point we wish to make is that many different and seemingly unrelated empirical findings which have accumulated over the years and all appear surprising and challenging from the the traditional point of view can be reinterpreted as converging evidence for the simple principles laid out in the above hypotheses.…”
Section: Introductionmentioning
confidence: 96%
“…In this case, the colour of the plate may have affected the perceived colour of the food by means of the well-known phenomenon of colour contrast. In the case of simultaneous colour contrast [29,30], an object seen in the foreground appears to have a different colour (or contrast) depending on the colour of the background [31,32]. This explanation had already been offered intuitively by Lyman: 'Simultaneous color contrast suggests that foods can be arranged in combinations so that their colors are subtly enhanced, subdued, or otherwise modified.…”
Section: On the Colour Of The Platementioning
confidence: 99%
“…Piqueras-Fiszman and her colleagues suggested that the colour of the plate may have affected the perceived colour of the food by means of colour contrast illusions. In the phenomenon of simultaneous contrast [18], a foreground object appears to have a different colour (or contrast) depending on the background colour [19,20]. According to such perceptuallybased interpretations, the colour of Piqueras-Fiszman et al's food would have appeared more intense against the background of the white plate than when served from the black plate.…”
Section: Cutlerymentioning
confidence: 99%